PENEGAKAN HUKUM TERHADAP DOKTER YANG MENOLAK PEMBUATAN VISUM ET REPERTUM DALAM TINDAK PIDANA PEMBUNUHAN ( Studi Kalimatan Barat ) - KUSMAYADI, SH. A.2121100, Jurnal Mahasiswa S2 Hukum UNTAN (Jurnal NESTOR Magister Hukum, 2013)
ABSTRACT This study discusses the demand for expert assistance in the investigation phase as mentioned in Article 120 paragraph(1) Criminal Procedure Code and the expert testimony Requests for assistance at this stage ofthe proceedings provided for in Article 180 paragraph (1) expert testimony KUHAP. About mentioned in the second chapter of the Criminal Procedure Code in above, given the sense of Article1, point to the 28th criminal Procedure Code, which states that: